A checklist of Thismia section Labiothismia (Thismiaceae), reinstated to include Asian species earlier placed in the neotropical T. sect. Glaziocharis - Nuraliev, Maxim S.; Sennikov, Alexander N. (Phytotaxa, 2024)
The paper contributes to a construction of a comprehensive sectional subdivision of the mycoheterotrophic genus Thismia through elucidating nomenclaturally correct application of the existing names and re-shaping the earlier proposed species groups in line with the ideas on phylogenetic relationships. The name Thismia sect. Glaziocharis widely used for a section accommodating certain Asian and Australian species is here demonstrated to be typified by the neotropical Thismia caudata (≡ Glaziocharis macahensis). This finding in conjunction with the phylogenetic views means that Thismia sect. Glaziocharis is to be applied to a neotropical group of the genus. Moreover, Thismia sect. Glaziocharis is the correct name for Thismia sect. Pyramidalis, since they are based on the same type species and the former name has a nomenclatural priority over the latter. The Asian species commonly placed into Thismia sect. Glaziocharis belong to a monophyletic group that has a single available name at the sectional rank, i.e. Thismia sect. Labiothismia. Thismia sect. Labiothismia is therefore formally reinstated, and a checklist of this section in the new circumscription is provided. The section is currently known to comprise 14 species, including a single North American species of Thismia, and the rest being distributed from India and Japan to Sumatra. Finally, a lectotype is designated for T. huangii.